Legal Regulation Risks and Insights Related to Cross-Border Flow of Data: Analysis based on the Measures for Standard Contracts for the Exit of Personal Information - Tian, Zixuan; Wen, Chenhao; Fan, Jinfeng (International Journal of Social Sciences and Public Administration, 2024)
The primary objective of this research is to ensure the secure and compliant transmission of personal information from China. To this end, the Chinese government has implemented the "Standard Contract Measures for the Export of Personal Information." This study employs both literature review and factor analysis methods to meticulously examine the potential risks in the practical implementation of these measures, and further suggests strategies to address the current challenges. Additionally, the study introduces foreign systems for reference, aiming to guide Chinese enterprises in circumventing legal risks associated with cross-border data flows and ensuring the security and compliance of personal information departing from the country. The findings of this research reveal that the existing legal framework for cross-border data flows in China has certain shortcomings, providing valuable insights for the improvement of China’s legal framework and related regulatory systems. Furthermore, it offers practical cautionary value for Chinese enterprises in their operations.